Tributação e desigualdade econômica: elementos para uma teoria da tributação redistributiva para o Brasil contemporâneo - Rebouças, Marcus Vinícius Parente (2019)
The National Tax System takes root and evolved guided by an ideology based on economic growth and fiscal neutrality. The legacy of this institutional inheritance is reproduced until the present day. Given the pattern of growth marked by extreme levels of concentration of income and wealth, the 1988 Constitution incorporated the reduction of economic inequalities as a fundamental objective. The empirical literature, however, remains categorical in pointing out that the country continues to be one of the most unequal social environments in the world, despite being among the largest global economies. The real challenge is to combine economic growth with more inclusive processes of prosperity. In “Capital in the 21st Century”, Thomas Piketty found, on the basis of long-run historical series, that when the rate of return on capital exceeds the rate of growth (g), a mechanism of divergence expressed in the relation “r> g”, capitalism automatically generates problematic economic inequalities. National institutional arrangements can in any case produce disparate patterns of income and wealth inequality. In the case of Brazil, the historically high levels are derived not only from unequal distributive processes, but also from faulty redistributive processes, as occurs due to the wicked and regressive Tax System. The theoretical justification of this work is based on the potential intrinsic and instrumental implications of the extreme economic inequalities in the moral, social, political, economic and legal planes and in their direct tax causes. In this context, the thesis is supported that, in order to compress the distributional gaps, the redefinition of the relationship between taxation and economic inequality plays an essential role and demands the reconstruction of the institutional profile of the Tax System through tax models that maximize the redistributive results of direct taxation through extrafiscality or extra-fiscal effects, and minimize the regressivity of indirect taxation, with a view to reducing the “r-g” difference, but also incorporate concerns about economic efficiency and fiscal equilibrium in the long run. The main objective is to promote a redistributive analysis of national taxation, especially in the field of direct taxes on income and wealth, and to develop a theoretical model of taxation that offers more adequate responses to the fiscal treatment of the distributive dilemmas of contemporary brazilian reality. Among the main findings of the research, it was verified that the reduction of the economic inequalities still figure as a fundamental objective in the present time and that the institutional necessity of institutional intervention in this sense persists; that the Constitution contains a contributory rationality that makes it possible to use taxation in line with this purpose; and that fiscal adjustments that increase the participation of direct taxes in the tax burden and reduce indirect taxes can theoretically evidence important redistributive results, as well as positive collection, allocative and financial consequences. Among the main findings of the research, it was verified that the reduction of the economic inequalities still figure as a fundamental objective in the present time and that the institutional necessity of the Social State in this sense persists; that the Constitution contains a contributory rationality that makes it possible to use taxation in line with this purpose; and that fiscal adjustments that increase the participation of direct taxes in the tax burden and reduce indirect taxes can theoretically evidence important redistributive results, as well as positive collection, allocative and financial consequences. From the methodological point of view, this is a bibliographical study, with theoretical contributions from the national and foreign literature, classical and contemporary, and incorporates reality cutbacks described by empirical research, makes comparisons, dialectically discusses arguments and develops critiques and proposals that theoretically can contribute to the evolution of brazilian taxation in a perspective that better matches equity and efficiency.